The Use of Cloud Computing in Supply Chain Management. - Dalewska, Izabela Paulina; Pavlíček, Antonín, 1977-; Böhmová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2015)
In the thesis, the author wanted to research the topic of implementation of cloud-based solutions in the area of Supply Chain Management. The first part is devoted to theoretical background of Cloud Computing -- different types of solutions are suitable for various kinds of business activity, and Supply Chain Management. In the second part, the author focused on an analysis of a company - FN Granum and searched for a Cloud Computing solution, which would be the best for it, taking into account current situation and future plans of the entity. Such extensive research resulted in a set of conclusions and recommendations, which may be helpful for any manager considering an implementation of cloud-based solutions into their supply chains.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses